2014
DOI: 10.5713/ajas.2013.13359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Procyanidin on Growth Performance and Immune Response in Pigs

Abstract: This study was performed to determine the effect of dietary supplementation of procyanidin on growth performance, blood characteristics, and immune function in growing pigs. In experiment 1 (Exp. 1), thirty-two crossbred pigs with an initial BW of 19.2±0.3 kg were allocated into 4 treatments for an 8-wk experiment: i) CON (basal diet), ii) MOS 0.1 (basal diet+0.1% mannanoligosaccharide), iii) Pro-1 (basal diet+0.01% procyanidin), and iv) Pro-2 (basal diet+0.02% procyanidin). Pigs fed Pro-1 and Pro-2 diets had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…), feed additives and antibiotics (Park et al . ), and farm management practices (Georgsson and Svendsen ). Protocols exploring gut microbial communities have evolved from simple selective plating methods to highly robust 16S rRNA gene‐based platforms, resulting in countless studies investigating the microbiota of the swine gut (Table ).…”
Section: The Diversity and Dynamics Of Lactobacillus In The Swine Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…), feed additives and antibiotics (Park et al . ), and farm management practices (Georgsson and Svendsen ). Protocols exploring gut microbial communities have evolved from simple selective plating methods to highly robust 16S rRNA gene‐based platforms, resulting in countless studies investigating the microbiota of the swine gut (Table ).…”
Section: The Diversity and Dynamics Of Lactobacillus In The Swine Gasmentioning
confidence: 99%
“…Previous studies have highlighted the importance of gut microbiota and their beneficial effects on the health and growth performance of hosts (Richards et al 2005). Gut microbial communities are influenced by a plethora of factors including host genotype or breed (Pajarillo et al 2014b), diet (Hong et al 2012), feed additives and antibiotics (Park et al 2014), and farm management practices (Georgsson and Svendsen 2002). Protocols exploring gut microbial communities have evolved from simple selective plating methods to highly robust 16S rRNA gene-based platforms, resulting in countless studies investigating the microbiota of the swine gut (Table 1).…”
Section: The Diversity and Dynamics Of Lactobacillus In The Swine Gasmentioning
confidence: 99%
“…Colistin sulfate and bacitracin zinc are commonly used growth-promoting antibiotics in farm production and are rarely assimilated by animal intestines. Antibiotics were shown to have an important effect on the growth of bacteria by suppressing bacterial wall synthesis [2], thereby improving the growth rate or reducing the incidence of diarrhea in piglets. A previous study showed that colistin sulfate could increase the activities of amylase, lipase and protease in broiler chickens [3].…”
Section: Introductionmentioning
confidence: 99%
“…The study showed oral administration of EGCG (0.5mg/ml) on the day of vaccination and continuation for the next 14 days resulted in increased antigen specific CD8+ and CD4+ T-cell mediated immune responses [127]. Effects of dietary supplementation of procyanidins on immunomodulation were studied in vivo [128]. The study reported that the secretion of LPS induced pro-inflammatory cytokines TNF-α, IL-1β and IL-6 were reduced in pigs fed a diet of 0.02% and 0.04% of procyanidins for 4 weeks [128].…”
Section: 4 Induction Of Cellular Immunomodulation By Flavonoidsmentioning
confidence: 99%
“…Effects of dietary supplementation of procyanidins on immunomodulation were studied in vivo [128]. The study reported that the secretion of LPS induced pro-inflammatory cytokines TNF-α, IL-1β and IL-6 were reduced in pigs fed a diet of 0.02% and 0.04% of procyanidins for 4 weeks [128]. …”
Section: 4 Induction Of Cellular Immunomodulation By Flavonoidsmentioning
confidence: 99%